PENYELIDIKAN GEOMAGNET BIJIH BESI DI WILAYAH JORONG KOTA BIRAH, KECAMATAN SUNGAI PAGU KABUPATEN SOLOK SELATAN - Ceni Febi Kurnia Sari; Yoszi Mingsi Anaperta (Universitas Negeri Padang, 2017)
The measureable magnetic field intensity variation is then interpreted in the form of the distribution of the magnetic material below the surface, then used as the basis for the prediction of possible geological conditions observed. The iron ore deposits in the survei area are generally interpreted as a form of sediment that fills the rock cavities, especially in limestone cavities. This occurs due to the geological structure that gives space for the placement of mineralization of ore deposits in the side rock zone. The value of this magnetic anomaly is located in the west, the eastern, and also in the north part. Keywords: Geomagnet Method, Iron Ore, Magnetic Properties, Magnetic Value, Magnetic Anomaly Value.